ผลของโปรแกรมการสร้างความเข้มแข็งทางใจ แบบกลุ่มต่อภาวะซึมเศร้าของผู้ป่วยจิตเภท - วรัญญา โหมดเกษม (สมาคมพยาบาลทหารบก, 2022)
The purposes of this quasi – experimental research were: 1) to compare depression of schizophrenic patients before and after received resilience enhancement group program, and 2) to compare depression of schizophrenic patients who received resilience enhancement group program and those who received regular nursing care. Forty samples were inpatients schizophrenic patients at Somdetchaopraya institute of psychiatry, 20 subjects were randomly assigned to experimental group and control group, who met the inclusion criteria. They were matched pair by gender, age, and psychiatric symptoms. The experimental group received resilience enhancement group program, and the control group received regular nursing care. Research instruments consisted; 1) The resilience enhancement group program, 2) Demographic questionnaire 3) The Thai version of Calgary Depression Scale for Schizophrenia (CDSS). All instruments were tested for content validity by 5 professional experts. The reliability of the 3rd instruments was reported by Cronbach’s Alpha coefficient of 0.85. Data were analyzed using descriptive statistics and t-test. Major findings were as follows: 1) Depression of schizophrenic patients who received resilience enhancement group program was significantly lower than before, at the .05 level. 2) Depression of schizophrenic patients who received resilience enhancement group program were significantly lower than those who received regular nursing care, at the .05 level.Conclusion: The result of this study support that the resilience enhancement group program can reduce the depression of schizophrenic patients.